Should I Cast an Ill-Informed Ballot? Examining the Contours of the Normative Obligation to Vote. Issue 5 (September 2019) - Doherty, David; Dowling, Conor M.; Gerber, Alan S.; Huber, Gregory A.
Proparticipatory norms play a central role in driving turnout. However, a broad norm that people are supposed to vote cannot explain why some people fail to participate or why rates of participation vary sharply across elections. We argue that the norm of voting extends beyond the mere act of voting. We present empirical evidence supporting the position that the social rewards for participating are conditional. The social rewards for casting an ill-informed vote are far smaller than those associated with casting an informed ballot. Moreover, some low-information voting strategies are viewed as less desirable than simply abstaining. Our findings illustrate an important constraint on the capacity of social norms to foster turnout. The effectiveness of efforts to translate norms into higher rates of turnout may depend on ensuring that voters are informed enough to cast a meaningful ballot.